2015
DOI: 10.4236/as.2015.68076
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Fiscal Benefits of <i>Rhizobium</i> Inoculation Supplemented with Phosphorus (P) and Potassium (K) in Climbing Beans (<i>Phaseolus vulgaris</i> L.) Grown in Northern Tanzania

Abstract: Both field and green house experiments were intended to investigate and evaluate the outcome of rhizobial inoculation supplemented with P and K on climbing beans production in northern Tanzania. The results obtained indicated that, inoculation using Rhizobium inoculants supplemented with fertilizers significantly (p ≤ 0.001) improved both vegetative and yield parameters of climbing beans varieties compared with control treatment. The economic analysis in rhizobium alone revealed a profit of US$ 2350 compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The nitrogenase BNF enzyme, which is found inside root nodules, is responsible for that; it converts atmospheric nitrogen into ammonia, which the plant subsequently absorbs (Bruijn 2015). Rhizobia inoculation significant increased shoot biomass and root biomass the number of root, yield components, number of pods per plant, number of grain per pod and yield per hactre of the climbing bean (Mmbaga et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…The nitrogenase BNF enzyme, which is found inside root nodules, is responsible for that; it converts atmospheric nitrogen into ammonia, which the plant subsequently absorbs (Bruijn 2015). Rhizobia inoculation significant increased shoot biomass and root biomass the number of root, yield components, number of pods per plant, number of grain per pod and yield per hactre of the climbing bean (Mmbaga et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Based on the results of the unweighted meta-analyses the average increase in grain yield and protein content was estimated at ~40% and ~10% respectively. This suggests that overall the use of inoculum is economically viable for farmers, since the cost of commercial seed inoculum products are now relatively low (usually less than 10 US $/ha) and recent economic analyses showed that relatively small increases in grain legume yields will significantly improve net-income for farmers, without economic benefits of increased residual-N (higher yields and/or lower fertilizer costs) in crops grown after legumes being taken into consideration [55][56][57][58][59]. However, since (i) crude protein content is estimated by measuring grain Ncontent and (ii) because grain N-content is correlated to total symbiotic N-fixation, the residual soil-N from inoculated crops with a 40% higher grain yield and 10% higher protein content, can also be estimated to be at least 40% higher compared with a non-inoculated crop.…”
Section: Effects Of Rhizobium Inoculation On the Performance Of Grain...mentioning
confidence: 99%
“…On the other hand, the element Mo is needed in the nitrate reductase enzyme to reduce nitrogen in nitrogen fixation in the root nodule tissue of soybean plants (Stiens et al, 2007). The element Mo is a component of the nitrate reductase enzyme, which plays a significant role in the assimilation of nitrogen nitrate (Mmbaga et al, 2015). High acidity (low pH) in ultisol soils and high Al saturation values can be neutralized by liming.…”
Section: Introductionmentioning
confidence: 99%